The Image of an Ideal Ukrainian Politician. Ukrainian National Idea - Oleg Bazaluk; Tamara Blazhevych (International Society of Philosophy and Cosmology, 2016)
Methodology of geophilosophy allowed the author to expand the understanding of Ukraine as the limitrophe State, through the territory of which runs the frontier of the confrontation between the two world cultures; explain the relationship between the totally corrupt Ukrainian authority and the geographic location of Ukraine. Prone to corruption the mentality of Ukrainian rulers and their Soviet nomenclatura past, to a large extent determined the course of history of Ukraine. Geophilosophy allowed the authors to formulate the Ukrainian national idea: Ukraine - Keeper, and the Ukrainians - the guardians of peace and a thousand years old culture in the western part of the Eurasian continent, as well as major cultural markers of Ukrainian identity.